ANALISIS STRUKTUR PASAR INDUSTRI KARET DAN BARANG KARET PERIODE TAHUN 2009 - Adisty Rizkyanti (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2010)
The purpose of this research is to acknowledge and to analyze the marketingstructure in the industry of rubber and the product itself in Indonesia duringthe year of 2009. The industrial rubber and the product itself are expected toplay a vital role in escalating more employment opportunities as well as apositive economical growth. With the role stated above, one can cultivatesand presents a developing direction so that it can compete with otherindustrial sectors in the economic perspective.The data obtained will be a secondary data. The instruments that are used toanalyze the marketing structure would be CRn (the concentration of ratio n)and IHH (Herfindahl-Hirschman Index). Subsequently the marketing structureof the rubber industry and the rubber product itself in Indonesia will also beanalyzed descriptively. The data is obtained from BPS and the nation’s Ministryof Industry.By analyzing the marketing structure using the concentration ratio methodattained from the four of the largest companies in the market share (CR4),one can fabricate a conclusion regarding the marketing structure of therubber industry and the product in Indonesia during the year of 2009 to bededuced as an ol igopoly marketing structure.